Analysis of Road Accidents Using Data Mining Techniques - Nidhi. R, Ms; Kanchana V, Ms (International Journal of Engineering and Technology, 2018)
RoadÂ Accident is an all-inclusive disaster with consistently raising pattern. In India according to Indian road safety campaign every minute there is a road accident and almost 17 people die per hour in road accidents. There are different categories of vehicle accidents like rear end, head on and rollover accidents. The state recorded police reports or FIRâ€™s are the documents which contains the information about the accidents. The incident may be self-reported by the people or recorded by the state police. In this paper the frequent patterns of road accidents is been predicted using Apriori and NaÃ¯ve Bayesian techniques. This pattern will help the government or NGOs to improve the safety and take preventive measures in the roads that have major accident zones.Â Â